"Choice-supportive bias" in science: Explanation and mitigation. (17th November 2021) - Kafaee, Mahdi; Marhamati, Hanie; Gharibzadeh, Shahriar
ABSTRACT: Mistakes in scientific research, their origins, and the possible solutions have always been noteworthy. On the other hand, researchers in some fields have focused on cognitive biases and their interventions in thinking and information processing. In this article, by bridging between these two issues, i.e., scientific research mistakes and cognitive bias, it will be first shown that scientific research requires scientists' choices in various stages such as subject selection, data treatment, theory determination, and technological design. Then, we show the involvement of choice-supportive bias in scientific inquiry as one of the potential cognitive limitations of science. Finally, three ways are discussed to mitigate the effects of this bias in science: more scores to self-criticism publications, recording of the shortcomings of the research by the researcher before publishing, and emphasizing control processes before researcher choices in scientific inquiry.